RELEVANT COSTING–TWO POINTS OF VIEW. - Ferrara, William L. (The Accounting Review, 1963)
The article focuses on two points of view concerning the cost categories relevant to income measurement. The ultimate conclusion of the argument is that the fixed costs of production are costs without service potential since their incurrence in one period has no effect on whether they will be incurred in the future. Variable production costs on the other hand do have service potential since their incurrence today will overcome the need for their incurrence in the future. The essence of the argument seems to be contained in the idea that the only costs, which will be reduced in the future because they are incurred today, are variable costs since the fixed costs will remain the same with or without the production of goods, which are included in the inventory. In other words, the value of the inventory is determined only by the extra costs occasioned by producing the inventory. These costs are variable costs of production since the fixed costs of production would be the same with or without the production of the inventory. The idea of opportunity costs is certainly much broader in its possible impact on accounting theory than its position in the Sorter-Horngren thesis of "relevant costing."